Causes of Rejection for Organ Donation by Family of Deceased Donor. (July 2018) - Seo, Jinwoo; Jeong, Youngsun; Kang, Hyungin; Kim, Sunhee; Cho, Wonhyun
Background: The number of notifications received at the Korea Organ Donation Agency (KODA) call center, is increasing every year from 1, 126 cases in 2012 to 2, 083 in 2016. But more than one fourth of them who were contacted by OPC (organ procurement coordinator) were rejected organ donation of their loved one. So we want to analyze the reasons of the rejection and use it for activation of organ donation campaign. Method: Of 8, 120 cases reported to KODA from 2012 to 2016, 3, 322 cases were provided information about brain death and organ donation using FCTT (Family Communication Tracking Tool). In FCTT, agreement of brain death organ donation and reasons for rejection were recorded. The reasons for rejection were classified into 10 items such as family members' understanding of brain death, attitude toward organ donation, procedural problems, religious problems, etc. Results: Among the total reported cases, the number of families that can be provided information and conducted counseling related to organ donation were 56% in 2012, 52.4% in 2013, 52% in 2014, 46.1% in 2015, and 42.1% in 2016. However, after performing organ donation counseling, 30.5% of donor's family in 2012, 25.7% in 2013, 26.8% in 2014, 27.9% in 2015 and 28.1% in 2016 rejected organ donation, so we could not proceed organ donation. The frequent reasons for rejecting the donation was 'they could not accept brain death status and want active treatment' in 34.7%, 'disagreement between family members' in 26.3%, 'ignorance about organ donation' (16.3%) and 'others' (7.5%). Other reasons even a small number were 'they do not want to damage the body of deceased family' (6.9%), 'we don't know the will of the deceased' (3.9%), 'misunderstanding about brain death and organ donation' (1, 4%), 'too complex about organ donation process' (1.3%), 'transfer the body to large hospital' (1.0%), and 'religious reasons' (0.6%) in that order. Conclusion: As seen from the results, many of the family members do not agree with the brain death state, and refuse the consent. This result is caused by present brain death definition in our domestic law. If the brain death is to be recognized as death regardless of organ donation, the donation rate can be expected to increase. In addition, if we respect the consent of next to kin, the number of rejection by disagreement between family members will be far decreasing. In order to effective public campaign and education, we can use these results and can change some of our national donation structure.